Evaluation and optimization of the derivatization reaction conditions of glyphosate and aminomethylphosphonic acid with 6‐aminoquinolyl‐N‐hydroxysuccinimidyl carbamate using reversed‐phase liquid chromatography. Issue 20 (25th August 2020) - Fontàs, Clàudia; Sanchez, Juan M.
Abstract: Due to the polar and ionic characteristics of glyphosate and its main metabolite, aminomethylphosphonic acid, a derivatization reaction is required before performing liquid chromatographic determination of these compounds. In this study, reaction conditions using 6‐aminoquinolyl‐N‐hydroxysuccinimidyl carbamate as the derivatization reagent are assessed. A two‐level full‐factorial design is applied here to optimize the derivatization time (ranging from 0.5 to 20 min) and temperature (from 24 to 55°C). It is found that neither of these two variables have a significant effect on the derivatization process and that the reaction is quantitatively achieved in a few seconds at room temperature (24°C). The results obtained indicate that derivatization reaction with 6‐aminoquinolyl‐N‐hydroxysuccinimidyl carbamate is achieved in milder conditions, with a faster kinetic reaction, than those required with the most conventional derivatization reagents used today, and the derivatives are more stable. It has been found that the most important parameter affecting the chromatographic separation is the pH of the mobile phase, as it has a significant effect on the retention time of the hydrolyzed excess of reagent. When ammonium acetate is used in the mobile phase, buffered solutions at pH around 5.0 are required.